Optimalisasi Peran Komunikasi HRD Melalui Program General Manager Table dalam Meningkatkan Kinerja Karyawan X Hotel Mojokerto - Fadyla Qurrotul Mahfudloh; Moch. Ichda Asyarin Hayau Lailin; Fatihatul Lailiyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The hotel industry is a service sector that relies heavily on the quality of human resources, so internal communication has a central role in maintaining smooth operations and improving staff performance. This study examines the implementation of Human Resource Development (HRD) communication through the General Manager Table Program at XHotel Mojokerto, which is designed as a medium for direct dialogue between management and employees. The program aims to accelerate the distribution of information, accommodate the aspirations of staff, and build more open and effective two-way communication. The research method uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, observations, and documentation studies. The study participants included General Managers, HRD, and hotel staff who participated in the program for a six-month period in 2025. Data analysis was carried out with reference to Mintzberg's organizational communication theory, which emphasizes the managerial role in the functions of monitoring, information dissemination, facilitation, and negotiation. The results of the study show that the General Manager Table Program contributes positively to the effectiveness of internal communication. Through this program, HRD not only plays the role of conveying information, but also as a dialogue facilitator that encourages active employee involvement. The program has been proven to improve communication transparency, speed up conflict resolution, and strengthen a sense of belonging among staff. The impact can be seen in increasing motivation, discipline, and more consistent work performance, while strengthening the harmonious relationship between management and employees in the work environment. The implication of this research is the need for sustainability and the development of similar programs as innovative HRD communication strategies. The application of this model can be a reference in building a positive work culture that supports productivity, service quality, and competitiveness of the hospitality industry amid global dynamics.